PENGARUH PEMBERIAN INSENTIF DAN MOTIVASI TERHADAP KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR SWASTA KOTA TERNATE - Khadijah, Siti; Hasan, Said; Haji, Sulfi Abd (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study aims to analyze the effect of incentives and motivation on the pedagogical competence of private elementary school teachers in Ternate City. Pedagogical competence, which is the ability of teachers to manage learning, is considered crucial to the quality of education. This study tests the hypothesis that incentives and motivation contribute significantly to improving this competence. The research method used is quantitative with a survey approach. The research sample consisted of private elementary school teachers in Ternate City who were selected through a simple random sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was carried out using multiple linear regression techniques to test the effect of incentives and motivation simultaneously and partially on teacher pedagogical competence. The results of the study indicate that there is an effect of incentives and motivation on the pedagogical competence of private elementary school teachers in Ternate City.